2020
DOI: 10.1194/jlr.s120000720
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin:cholesterol acyltransferase: symposium on 50 years of biomedical research from its discovery to latest findings

Abstract: Lecithin:cholesterol acyltransferase (LCAT) converts free cholesterol to cholesteryl esters in the process of reverse cholesterol transport. Familial LCAT deficiency (FLD) is a genetic disease that was first described by Kaare R. Norum and Egil Gjone in 1967. This report is a summary from a 2017 symposium where Dr. Norum recounted the history of FLD and leading experts on LCAT shared their results. The Tesmer lab shared structural findings on LCAT and the close homolog lysosomal phospholipase A2. Results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Nascent HDL particles transfer lipids to both apoB-containing particles and the plasma resident HDL pool. The unesterified cholesterol content of the nascent HDL pool is transferred to apoB-containing particles, which then redistributes to HDL for its effective esterification by lecithin-cholesterol acyltransferase (LCAT) [39]. HDL-associated cholesteryl-esters are partially transferred back to apoB-containing lipoproteins by cholesterol ester transfer protein (CETP) [40].…”
Section: Hdl Biosynthesis and Remodelingmentioning
confidence: 99%
“…Nascent HDL particles transfer lipids to both apoB-containing particles and the plasma resident HDL pool. The unesterified cholesterol content of the nascent HDL pool is transferred to apoB-containing particles, which then redistributes to HDL for its effective esterification by lecithin-cholesterol acyltransferase (LCAT) [39]. HDL-associated cholesteryl-esters are partially transferred back to apoB-containing lipoproteins by cholesterol ester transfer protein (CETP) [40].…”
Section: Hdl Biosynthesis and Remodelingmentioning
confidence: 99%
“…The cardiovascular risk associated with LCAT de ciency syndromes has been a matter of debate for a number of years. A severe de ciency of HDL-C in LCAT de cient carriers would be expected to increase their risk of developing coronary heart disease (83). Oldoni et al, have compared carotid intima media thickness between 33 heterozygous FLD subjects and 41 heterozygous FED subjects (102).…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that this discrepancy was related to the capacity of LCAT to esterify cholesterol on apolipoprotein B-containing lipoproteins-this capacity is lost in FLD, but is unaffected in FED. In a study of Italian FLD families, the inheritance of a mutated LCAT genotype had a remarkable gene-dose dependent effect in reducing carotid IMT, whereas a subgroup of these carriers also showed normal ow-mediated dilation (65,83,103). A Mendelian randomization study in 54,500 subjects concluded that common genetic variation in LCAT resulting in decreased HDL-C levels, did not associate with an increased risk of ischemic cardiovascular disease (104).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations